A Needs Driven Model of Workplace Social Effectiveness in Adults With Disabilities. (October 2018) - Phillips, Brian N.; Reyes, Antonio; Kriofske Mainella, Alexandra M.; Kesselmayer, Rachel F.; Jacobson, Joseph D.
Social effectiveness is central to workplace success. Yet, surprisingly little is known about the factors that influence effectiveness in managing the social requirements of the workplace. This study provides a preliminary analysis of a model of workplace social effectiveness for adults with disabilities. A total of 330 adults with disabilities participated in an online, cross-sectional research study. Researchers used several measures to assess the extent to which latent variables representing communal and positive approaches to social situations influenced workplace social effectiveness and whether that relationship was mediated by the ability to connect with others. Results from a structural equation model analysis suggest that both a communal and positive social approach predict workplace social effectiveness. The ability to connect with others partially mediated relationships between both communal and positive approaches and workplace social effectiveness. Although the cross-sectional and self-report nature of this study limits the conclusions that can be drawn, the findings lay a groundwork for further model testing and clinical interventions in rehabilitation counseling services. The results offer an alternative socioemotional approach for identifying and intervening on workplace social effectiveness that can be applied to adults with disabilities.